Genetic Risk of Azoospermia Factor (AZF) Microdeletions in Idiopathic Cases of Azoospermia and Oligozoospermia in Central Indian Population - PRAFULLA S. AMBULKAR; RAMJI SIGH; MVR REDDY; POONAM S. VARMA; DILIP O. GUPTA; MORESHWAR R SHENDE; ASOKE K PAL (Journal of Clinical and Diagnostic Research, 2014)
Background: Genetic factors cause about 15% of male infertility. Azoospermia factors (AZFa, AZFb, and AZFc) present on Yq are most important for spermatogenesis. We have made an attempt to evaluate the frequencies of microdeletions of AZFa, AZFb, AZFc in idiopathic cases of azoospermia and oligozoospermia from central Indian population. Materials and Methods: We have analyzed a total of 156 subjects (95 oligozoospermia and 61 azoospermia) & 50 control subjects. DNA samples were analyzed for microdeletions of Y chromosome by PCR-screening of 18 sequences-tagged-site (STS) markers from different region of the AZF on Yq and SRY on Yp. Results: Out of 156 cases analyzed, 13 (8.33%) subjects (8 azoospermia and 5 oligozoospermia) showed partial deletion of AZF regions, of which deletion in AZFc region was the most common (84.6%) followed by AZFb (15.4%) and AZFa (15.4%). The sites and sizes of deletions varied among patients. Histological study of the testicular tissue of the available subjects, who showed microdeletions of Y chromosome, showed spermatogenic arrest at different stages. The frequency of Y chromosome microdeletion in our subjects was 8.33%. Conclusion: Some Indian studies reported low frequencies of microdeletions than that of our result. We suggest that the frequency of deletions may be affected by the involvement of different genetic factors, ethnic population and different geographical regions. PCR based Y chromosome screening for microdeletions will be useful and great help to infertility clinics for genetic counselling and assisted reproduction.